(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Today, there is a pressing need to set aside arable land in addition to meeting rising demand forit to accommodate residential, commercial, and industrial development across the board. That’s whythere’s a recent surge in the construction of skyscrapers. Wind and earthquakes exert lateral stresses onthese high-rises. This research also makes an attempt to simulate the shear wall’s interaction with theRC frame in two dimensions for buildings of 20, 30, and 35 stories. Two outside frames with shear wallsare treated as a single frame with double stiffness, strength, and weight in the corresponding simplified2-dimensional model. It is assumed that the internal frames without a shear wall have the same stiffness,strength, and weight, hence they are represented as a single frame. Every story in the model requires astiff link to connect the frames. The lateral force distribution between the outside frame with a shear walland the inside frame without a shear wall is examined using a 2-dimensional plane frame model.Analysis shows that up to the lowest seven or eight stories, the frame with shear wall bears more thanhalf the load, and the bottom three stories bear almost 75 of the whole story’s shear. This researchexamines a 30-story skyscraper with and without shear wall apertures. Specifically, dynamic analysismakes use of the response spectrum approach.